IMPACT OF RESPONSIBILITY ACCOUNTING TREATMENT ON COST CONTROL EFFECTIVENESS - Ovianti, Rima; Meirina, Elsa (LPPM Universitas Bina Bangsa, 2025)
This study aims to determine the impact of responsibility accounting treatment on the effectiveness of cost control. The population in this study were all employees of PT Andalan Mitra Prestasi. This study used purposive sampling technique with 28 respondents. This research is designed with a quantitative approach, because the variables used are numerical. The variables in this study are measured by numbers and data analysis with statistical techniques, namely multiple linear regression analysis using SPSS software version 29. The results showed that organizational structure and budget planning partially had a significant negative effect on the effectiveness of cost control, while the implementation of control and reporting partially had a significant positive effect on the effectiveness of cost control. And simultaneously organizational structure, budget planning, implementation of control and reporting have a significant positive effect on the effectiveness of cost control.